2003
DOI: 10.1161/01.cir.0000103624.14436.4b
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory/Antiinflammatory Properties of High-Density Lipoprotein Distinguish Patients From Control Subjects Better Than High-Density Lipoprotein Cholesterol Levels and Are Favorably Affected by Simvastatin Treatment

Abstract: Background-The inflammatory/antiinflammatory properties of HDL were compared with HDL cholesterol in 2 groups of patients and in age-and sex-matched control subjects. Methods and Results-Group 1 consisted of 26 patients not yet taking a statin who presented with coronary heart disease (CHD) or CHD equivalents by National Cholesterol Education Program Adult Treatment Panel III criteria studied before and 6 weeks after 40 mg/d of simvastatin. Group 2 consisted of 20 patients with documented CHD and HDL cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
477
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(502 citation statements)
references
References 25 publications
20
477
0
5
Order By: Relevance
“…Long‐term statin exposure increases HDL's anti‐inflammatory and antioxidant capacity 23, 26, 38. In our study, the strength of the association between high HDL cholesterol concentration and decreased AKI was greatest among patients receiving long‐term statin therapy, was related to dose of long‐term preoperative statin, and was enhanced among patients randomized to receive perioperative atorvastatin.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Long‐term statin exposure increases HDL's anti‐inflammatory and antioxidant capacity 23, 26, 38. In our study, the strength of the association between high HDL cholesterol concentration and decreased AKI was greatest among patients receiving long‐term statin therapy, was related to dose of long‐term preoperative statin, and was enhanced among patients randomized to receive perioperative atorvastatin.…”
Section: Discussionmentioning
confidence: 48%
“…In a similar manner among cardiac surgery patients, a low HDL cholesterol concentration could increase the risk of organ dysfunction, including postoperative AKI, and conversely, a high concentration of HDL cholesterol could decrease the risk of postoperative AKI. Furthermore, in patients undergoing cardiac surgery, who are frequently prescribed statins, any effect of HDL on postoperative AKI risk might be altered by statin exposure, because statin treatment both modestly increases HDL cholesterol concentration and increases the anti‐inflammatory and antioxidant capacities of HDL 23, 24, 25, 26…”
mentioning
confidence: 99%
“…159 Moreover, 6-week therapy with 40 mg per day simvastatin in patients with coronary heart disease resulted in a significant improvement in the ability of HDL to inhibit oxidation and monocyte chemotactic activity released by cells after stimulation by oxidized LDL. 160 In a small study involving dyslipidemic patients, treatment with 2 mg pitavastatin for 4 weeks increased serum concentration of HDL-cholesterol levels by 9% and the HDL phospholipid content by 8%. 161 This was accompanied by similar increases in the capacity of the HDL fraction of serum to remove cholesterol from human macrophages and HDL-associated PON1 activity.…”
Section: Statinsmentioning
confidence: 99%
“…Because of its high concentration, carrying a dysfunctional HDL may be more dangerous for vascular health than having low levels of functional HDL. Ansell et al (22) showed that patients with CHD and HDL-C greater than 85 mg/dL carry dysfunctional HDL. A recent analysis of The Incremental Decrease in Endpoints through Aggressive Lipid Lowering trial (IDEAL) and European Prospective Investigation of Cancer-Norfolk observational study determined that the classic inverse correlation between HDL-C and CHD risk is not sustained when evaluating subjects with HDL greater than 70 mg/dL who appear to have increased CHD risk even when on statin therapy (23).…”
Section: Hdl Functionmentioning
confidence: 99%